The relationship between organisational attributes and internal audit effectiveness - Bednarek, Piotr (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
Prior studies show that the degree of internal audit effectiveness tends to vary with country- and organisation-level dynamics in an internal audit environment. The antecedents of internal audit effectiveness appear not fully explored as yet. This study, based on institutional theory, is aimed at investigating the relationship of internal audit effectiveness with two organisational attributes, i.e. organisational category and organisational size. To this end, a postal survey and an online survey were conducted among internal auditors in Poland. The research results show that although internal audit effectiveness does not significantly differ between public sector and private sector organisations, larger organisations in private sector have established more effective internal audit departments than their counterparts in smaller organisations. However, in the public sector the size of organisations is not related to internal audit effectiveness
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 474, s. 11-24
Keywords: effectiveness; internal audit; public sector; private sector; skuteczność; audyt wewnętrzny; sektor publiczny; sektor prywatny